Molecular dynamics simulation of mahkota dewa (phaleria macrocarpa) extract in subcritical water extraction process - Nurmaryam Aini, Hashim; Siti Kholijah, Abdul Mudalip; Noorlisa, Harun; Rohaida, Che Man; Siti Zubaidah, Sulaiman; Zatul Iffah, Mohd Arshad; Shalyda, Md Shaarani (IOP Publishing, 2018)
Mahkota Dewa (Phaleria Macrocarpa), a good source of saponin, flavanoid, polyphenol, alkaloid, and mangiferin has an extensive range of medicinal effects. The intermolecular interactions between solute and solvents such as hydrogen bonding considered as an important factor that affect the extraction of bioactive compounds. In this work, molecular dynamics simulation was performed to elucidate the hydrogen bonding exists between Mahkota Dewa extracts and water during subcritical extraction process. A bioactive compound in the Mahkota Dewa extract, namely mangiferin was selected as a model compound. The simulation was performed at 373 K and 4.0 MPa using COMPASS force field and Ewald summation method available in Material Studio 7.0 simulation package. The radial distribution functions (RDF) between mangiferin and water signify the presence of hydrogen bonding in the extraction process. The simulation of the binary mixture of mangiferin:water shows that strong hydrogen bonding was formed. It is suggested that, the intermolecular interaction between OH2O••HMR4(OH1) has been identified to be responsible for the mangiferin extraction process.